2019
DOI: 10.1093/jamiaopen/ooz003
|View full text |Cite
|
Sign up to set email alerts
|

Electronic health record (EHR) training program identifies a new tool to quantify the EHR time burden and improves providers’ perceived control over their workload in the EHR

Abstract: Objective To understand if providers who had additional electronic health record (EHR) training improved their satisfaction, decreased personal EHR-use time, and decreased turnaround time on tasks. Materials and Methods This pre-post study with no controls evaluated the impact of a supplemental EHR training program on a group of academic and community practice clinicians that previously had go-live group EHR training and 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 30 publications
1
78
0
Order By: Relevance
“…11,12 Some of this difference may be attributed to differences in methodologies, as one study used self-report to determine afterhours work, 11 which might be an inaccurate estimate of objectively measured EHR time outside of clinic. 30 Another study normalized EHR time to a full-time physician and included weekday and weekend use in after-hours totals. 12 Nonetheless, physicians in this study had relatively low faceto-face time and patients-per-hour requirements compared with other organizations, which may have resulted in lower after-hours EHR use and limit the generalizability of our findings to settings with higher productivity requirements.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Some of this difference may be attributed to differences in methodologies, as one study used self-report to determine afterhours work, 11 which might be an inaccurate estimate of objectively measured EHR time outside of clinic. 30 Another study normalized EHR time to a full-time physician and included weekday and weekend use in after-hours totals. 12 Nonetheless, physicians in this study had relatively low faceto-face time and patients-per-hour requirements compared with other organizations, which may have resulted in lower after-hours EHR use and limit the generalizability of our findings to settings with higher productivity requirements.…”
Section: Discussionmentioning
confidence: 99%
“…In efforts to better understand and improve provider efficiency, the team at Stanford discovered that individualized training can improve providers’ self-perceived knowledge and use of EHR tools and also improve their satisfaction with their EHR workload. 8 , 9 It is well known that lack of mastery contributes to feelings of burnout, and thus it is logical that efforts to improve an individual’s mastery of the EHR may have a positive impact on their wellness. 10 While surveys can give a sense whether interventions make an impact, they are time-consuming to administer and are not always fully representative of a given population.…”
Section: Ehr Optimization Programs: Targeting Burnout and Getting “Bumentioning
confidence: 99%
“…The Stanford team was able to identify that more after-hours time correlated with a worse provider EHR experience, and therefore was a prime candidate for an EHR-data-drive metric to track outcomes. 9 …”
Section: Ehr Optimization Programs: Targeting Burnout and Getting “Bumentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in this study reported using shortcuts, such as completing electronic documentation at the end of their shifts rather than at the point-of-service (Rathert et al, 2017). DiAngi et al (2019) concluded that training to use an EHR system improved health care practitioners' perceived control of their workload while employing the EHR; however, health care practitioners continued to use the EHR outside of clinic hours. Jamieson et al (2016) concluded in a quantitative, blinded randomized crossover study that internal medicine physicians who used an EHR system had a greater quality of admission notes than those who used handwritten documentation.…”
Section: Current Evidence For Electronic Documentationmentioning
confidence: 99%